Black stem by Phoma macdonaldii affected ecophysiological components that determine grain yield in sunflower (Helianthus annuus L.) - Quiroz, Facundo José (2014)
Black stem (BS) of sunflower (Helianthus annuus L.) by Phoma macdonaldii has been reported in many production areas of the world associated to losses in grain yield. Their symptoms could be confounded with natural leaf senescence because they appear during the reproductive period. The objective of this work was to evaluate the effect of BS by P. macdonaldii on grain yield and the ecophysiological components determining it. Two field experiments were conducted under natural inoculation of P. macdonaldii. Two hybrids were protected or not with a combination of leaf fungicides. Severity of BS, leaf area, leaf senescence, intercepted PAR and dry matter were periodically measured. Nitrogen nutrition index was estimated at flowering. At physiological maturity, BS incidence, grain number and weight, and oil concentration were also measured. Presence of other diseases was low or null. Incidence of BS ranged from 2.9% to 49% within the protection treatments, hybrids and experiments. The protected treatment diminished BS in both hybrids and experiments in comparison with the unprotected one. Plants from protected treatment showed higher leaf area, leaf area duration, intercepted PAR, radiation use efficiency, dry matter and grain yield and their components, than those from unprotected treatment. Oil concentration was not affected by the disease. Differences in all studied variables were mainly supported for differences in mid and upper leaves. Black stem was related to premature leaf senescence and thus to reduction of intercepted radiation. An effect not only on the efficiency of radiation interception but also in the efficiency of the radiation conversion was observed.